A chromosome-level reference genome of Ensete glaucum gives insight into diversity and chromosomal and repetitive sequence evolution in the Musaceae - Wang, Ziwei; Rouard, Mathieu; Biswas, Manosh; Droc, Gaetan; Cui, Dongli; Roux, Nicolas Stephan M.; Baurens, Franc-Christophe; Ge, Xue-Jun; Schwarzacher, Trude; Heslop-Harrison, J.S.; Liu, Qing (Oxford University Press, 2022)
Ensete glaucum (2n = 2x = 18) is a giant herbaceous monocotyledonous plant in the small Musaceae family along with banana (Musa). A high-quality reference genome sequence assembly of E. glaucum is a resource for functional and evolutionary studies of Ensete, Musaceae, and the Zingiberales.